Regulatory effect of Pseudomonas aeruginosa mannose-sensitive hemagglutinin on inflammation and immune function in percutaneous nephrolithotomy patients with upper urinary tract calculi complicated with infection - Zhao, Yuan; Zhang, Yafei; Liu, Jianhe (Frontiers in Immunology, 2023)
Objective： To study the effect of an injection of Pseudomonas aeruginosa on inflammation and immune function in patients with upper urinary tract calculi complicated by infection who have undergone percutaneous nephrolithotomy. Material and Methods： We retrospectively recorded the clinical data of patients with upper urinary tract calculi complicated by infection who have undergone Percutaneous nephrolithotomy(PCNL) in the Department of Urology, 2nd Affiliation Hospital of Kunming Medical University, from March to December 2021. Clinical data include general condition, laboratory index, CT, postoperative body temperature, heart rate, respiration, SIRS, sepsis, etc. Patients were divided into treated and control groups according to whether they had received a preoperative Pseudomonas aeruginosa injection. The two groups were compared for indices of inflammation and complications of infection after PCNL. Pre- and post-operative lymphocyte subsets and immunoglobulin changes were compared. Results： 115 patients were included in the study, including 43 in the treatment group and 72 in the control group. After Propensity Score Matching, 90 patients were divided into treatment (n=35) and control (n=55) groups. The postoperative inflammation index was higher in the treatment group than in the control group (P<0.05). The incidence of postoperative SIRS was higher in the treatment group than control (P<0.05). There were no cases of sepsis in either group. The double-positive T cells lymphocyte subsets were higher in the treatment group than in the control group ((P<0.05). Pre- and post-operative changes in immune function: total T lymphocyte count reduced, NK and NKT cell count increased in the control group, double-positive T cell count increased in the treatment group, IgG, IgA, IgM, complement C3 and C4 count reduced in both groups post-operatively. Conclusion： This study found that patients with upper urinary tract calculi and infection treated with antibiotic-based Pseudomonas aeruginosa before percutaneous nephrolithotomy had an increased inflammatory response after surgery, which may play a role in the prevention and treatment of sepsis. The percentage of double-positive T cells in the peripheral blood was increased after Pseudomonas aeruginosa treatment, which may have an immunomodulatory and protective effect in PCNL patients with stones complicated by infection.